Chemical accident - Lampton, Christopher (Brookfield, Conn. : Millbrook Press, 1994)
Discusses the causes of chemical accidents, describes such disasters as the Bhopal catastrophe, and examines how such accidents can be prevented.
Includes bibliographical references (p. 45) and index.
Keywords: Chemical industry -- Accidents -- Juvenile literature; Chemical industry -- Accidents